RELATIONSHIP BETWEEN PARAMETERS OF THE LUMBAR FACET JOINTS IN A LONG-TERM POSTOPERATIVE OUTCOME - Byvaltsev,Vadim Anatol'evich (2018)
ABSTRACT Objective: To analyze the impact of the relationship between tropism and angulation of the lower lumbar facet joints on a remote clinical outcome after dynamic and rigid surgical interventions. Methods: Patients with degenerative diseases of the lower lumbar spine were subdivided into three groups, according to the method of surgical treatment: 1) (n=48) the use of an artificial prosthesis intervertebral disc (IVD); 2) (n=42) the use of interbody fusion combined with transpedicular and transfacet stabilization; 3) (n=51) the use of interbody fusion and bilateral transpedicular stabilization. Analysis was performed of the remote clinical parameters and neuroimaging characteristics before the operation was performed. Results: When analyzing clinical and instrumental parameters, a significant correlation was found between the long-term outcomes of surgical treatment on the VAS and Oswestry scales and the neuroimaging data on angulation and tropism of the facet joints (FJ). Conclusions: The data obtained testify to the importance of preoperative diagnosis of tropism and angulation of the lower lumbar facet joint, which enables differentiated surgical tactics to be selected, and remote clinical outcomes to be optimized. In the presence of neuroimaging parameters of Facet Joint angulation of less than 600, regardless of the presence of tropism, it is possible to perform total arthroplasty of IVD. When neuroimaging parameters of Facet Joint angulation of more than 600 are detected, rigid stabilization of the operated segment is recommended, while in the absence of tropism of Facet Joints, a contralateral transfacetal fixation is possible; in the presence of tropism, it is expedient to perform bilateral transpedicular stabilization. Level of Evidence II; Prognostic Studies—Investigating the Effect of a Patient Characteristic on the Outcome of Disease.